Pengaruh Gaya Kepemimpinan Transformasional dan Etos Kerja Terhadap Kinerja Karyawan CV Raja Jaya Motor Maumere - Maria Kristina; Imanuel Wellem; Paulus Juru (Jurnal CUAN Universitas Nusa Nipa Maumere, 2025)
This study aimed to (1) describe Employee Performance, Transformational Leadership Style, and Work Ethic; (2) analyze the influence of Transformational Leadership Style and Work Ethic on Employee Performance, both partially and simultaneously. The population in this study consisted of 45 employees of CV Raja Jaya Motor Maumere. Using Slovin's formula, the sample for this research included 30 employees. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, specifically multiple linear regression. Hypothesis testing was c onducted using the F-test and t-test. The descriptive analysis results showed that the Employee Performance variable was categorized as good, the Transformational Leadership Style variable was also categorized as good, and the Work Ethic variable was categorized as good. The t-test results indicated that, partially, the Transformational Leadership Style variable had a positive and significant effect on Employee Performance. Additionally, the Teamwork variable also had a positive and significant effect on Employee Performance. The F-test results showed that, simultaneously, the Transformational Leadership Style and Teamwork variables significantly influenced Employee Performance. The determination analysis revealed that the two independent variables in this study were able to explain 37.2% of the variation in Employee Performance at CV Raja Jaya Motor Maumere.